Features and clinical significance of tertiary lymphoid structure in cutaneous squamous cell carcinoma. (4th August 2022) - Wu, Y.H.; Wu, F.; Yan, G.R.; Zeng, Q.Y.; Jia, N.; Zheng, Z.; Fang, S.; Liu, Y.Q.; Zhang, G.L.; Wang, X.L.
Abstract: Background: Tertiary lymphoid structure (TLS) plays an important role in antitumour immunity, largely reflecting the prognosis. However, its clinical implication in cutaneous squamous cell carcinoma (cSCC) remains unknown. Objectives: To explore the features of TLS in cSCC and its association with clinicopathological characteristics. Methods: Two independent RNA‐seq data of cSCC were used to investigate the tumour immune microenvironment, as well as TLS‐related chemokines and cytokines. The density and location of TLSs were assessed in a total of 82 cSCC patients, and the clinicopathologic association was examined. Results: Bioinformatics analysis showed that a large amount of immune cell infiltration and significant up‐regulation of TLS‐related chemokines were observed in cSCC. Histologically, TLSs appeared as highly organized structures in 72 (87.8%) cases with different levels of density and maturation, among which 14 cases were in low‐density group and 58 cases were in high‐density group. Clinically, the presence of TLS was prominently associated with better degree of histopathological grades and higher level of sun exposure. Furthermore, the presence of intratumoral TLS was associated with lower lymphovascular invasion. Conclusions: TLS is highly organized in cSCC, and the presence of TLS is a positive prognostic factor for cSCC, which will provide a theoretical basis for the future diagnostic and therapeutic value in cSCC.